2020
DOI: 10.1038/s41398-020-00938-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connectomes underlying response to trauma-focused psychotherapy in post-traumatic stress disorder

Abstract: Although trauma-focused cognitive behavior therapy (TF-CBT) is the frontline treatment for post-traumatic stress disorder (PTSD), up to one-half of patients are treatment nonresponders. To understand treatment nonresponse, it is important to understand the neural mechanisms of TF-CBT. Here, we used whole-brain intrinsic functional connectivity analysis to identify neural connectomic signatures of treatment outcome. In total, 36 PTSD patients and 36 healthy individuals underwent functional MRI at pre-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…In adults treated with prolonged exposure, Etkin, et al [23] found a classification accuracy of >85%, using a combination of pre-treatment rs-fMRI connectivity within the ventral attention network and delayed recall performance in a verbal memory task. In another study, pre-treatment functional connectivity within- and between-the default mode, dorsal attention, cingulo-opercular, salience, and central executive network during task-free fMRI predicted response to TF-CBT with an accuracy of 71.4% [20]. Finally, we have previously shown the feasibility of the same approach as outlined here to predict response to trauma-focused therapy in veterans with PTSD with 81.4% accuracy [17], with an ICN centered on the pre-supplementary motor area providing the best predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adults treated with prolonged exposure, Etkin, et al [23] found a classification accuracy of >85%, using a combination of pre-treatment rs-fMRI connectivity within the ventral attention network and delayed recall performance in a verbal memory task. In another study, pre-treatment functional connectivity within- and between-the default mode, dorsal attention, cingulo-opercular, salience, and central executive network during task-free fMRI predicted response to TF-CBT with an accuracy of 71.4% [20]. Finally, we have previously shown the feasibility of the same approach as outlined here to predict response to trauma-focused therapy in veterans with PTSD with 81.4% accuracy [17], with an ICN centered on the pre-supplementary motor area providing the best predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, relatively few studies have investigated the relationship between treatment-response and large-scale brain network connectivity. In adults with PTSD pre-treatment difference between trauma-focused psychotherapy responder and non-responder groups have been observed in activity and functional connectivity both during resting-state and task-based fMRI [16-20]. Findings from these studies suggest that activity and connectivity within regions and networks involved in working memory as well as emotional processing and modulation differed between responders and non-responders [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present fMRI study was designed to explore how an effective response to traumatic memory reactivation therapy (with or without propranolol) for intrusive symptoms in PTSD could modulate AI causal influences over the brain. Many fMRI studies measured pre/post functional connectivity using correlations (Etkin et al, 2019; Korgaonkar et al, 2020; Santarnecchi et al, 2019; Zhu et al, 2018), but only a limited number of studies reported effective connectivity changes in PTSD (Fonzo et al, 2021; Rangaprakash et al, 2018b), with no particular focus on intrusive symptoms in a whole brain approach. We focused on the AI since this region is known to be: (i) a central integration hub serving sensory, emotional, motivational and cognitive functions, (ii) potentially involved in re-experiencing trauma.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many patients, even successful EBT in the clinic is followed by a relapse of symptoms in the course of the patients' daily lives. The pathophysiological mechanisms underlying such interindividual variations in vulnerability to relapse remain unknown (Etkin et al 2019;Zhutovsky et al 2019;Korgaonkar et al 2020), and a crucial endeavor in fear extinction research is to identify clear biomarkers of such differences.…”
Section: Introductionmentioning
confidence: 99%